The cloning sourcebook - Klotzko, Arlene Judith (Oxford University Press, 2003)
PART I. The Science of Cloning 1. Voices from Roslin: The Creators of Dolly Discuss Science, Ethics, and Social Responsibility, Arlene Judith Klotzko2. Mammalian Cloning by Nuclear Microinjection, A.C.F. Perry3. On Recent Developments in Mammalian Nuclear Transplantation Cloning, Steen Willadsen4. Dolly Mice, Anne McLaren5. Controversy over Dolly's Provenance, Alan Colman6. Thinking Twice, or Thrice, about Cloning, Lee Silver7. Would Cloned Humans Really Be Like Sheep?, Leon EisenbergPART II. The Context of Cloning 8. Cloning in the Popular Imagination, Dorothy Nelkin and M. Susan Lindee9. The.